Molecular epidemiology of Campylobacter jejuni infection in Israel—a nationwide study. (December 2016) - Weinberger, M.; Moran-Gilad, J.; Rokney, A.; Davidov, Y.; Agmon, V.; Peretz, C.; Valinsky, L.
Abstract: The incidence of Campylobacter infection in Israel, particularly among children <2 years of age, has risen over the last decade and became one of the highest among industrialized countries. This study explored the molecular epidemiology of Campylobacter jejuni in Israel over a decade (2003–2012) using multilocus sequence typing (MLST) combined with demographic metadata. Representative clinical isolates (438) from a large national repository together with selected veterinary isolates (74) were subject to MLST. The distribution of age groups, ethnicity and clinical source across various genotypes was evaluated using Poisson modelling. The 512 studied isolates were assigned 126 distinct sequence types (STs) (18.8% novel STs) grouped into 21 clonal complexes (CCs). Most human, poultry and bovine STs clustered together in the leading CCs. Three dominant STs (ST21, ST6608, ST4766) were detected only since 2006. Patients infected with the leading CCs were similarly distributed along densely populated areas. The frequency of blood isolates was higher in patients infected with CC353 (relative rate (RR) = 2.0, 95% CI 1.03–3.9, adjusted p value (adj.p) 0.047) and CC42 (RR = 4.4, 95% CI 1.7–11.6, adj.p 0.018) and lower with CC257 (RR = 0.3, 95% CI 0.1–0.9, adj. p 0.047). The distribution of age groups and ethnicity also varied across the leading CCs. In conclusion, C. jejuni isolates in a national sample appeared highly diverse with a high proportion of new STs. Phylogenic analysis was compatible with poultry and cattle as possible food sources of clinical infection. Demographic characteristics of the infected patients coupled with strain invasiveness across different genotypes revealed a complex epidemiology of C. jejuni transmission in Israel.